Sejarah Media Penafsiran di Indonesia - Muhammad Miftahuddin (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2020)
The development of science always walk on the roal with the media used. This also give color the history of tafsir in Indonesia. Marshall McLuhan said there are at least four divisions of media development in general, the tribal age, the age of literacy, the print age, and the electronic age. Based on the classifications of the McLuhan media era, it can be seen how the history of tafsir in Indonesia developed according to the media used, first, the era of oral tafsir which coincided with the islamization process where the application of Al-Qur’an values was conveyed through speaking. Secondary, the era of written tafsir which began to use paper as the medium and us handwriting. Third, the era of printed tafsir which uses a printing press as its main characteristic, such as books, magazines, and others. Fourth, the era of electronic tafsir which began to use electronic media such as tv and radio. Fifth, the era of online tafsir which is the development of the era of electronic tafsir. In this era, interpretation is carried out through online media such as YouTube, websites, social media and others.